Роль та значення копірайтингу в маркетингу - Ткачук (Стахурська), Світлана Валеріївна; Стахурський, Валерій Олександрович (My University, 2023)
У статті розглядається роль і значення копірайтинг у маркетинговій діяльності підприємств, досліджуються точки дотику копірайтингу/дизайну і маркетингу в аспекті окремих елементів маркетинг-міксу. Найбільша роль копірайтингу та дизайну відчувається при формуванні та реалізації маркетингової політики просування: рекламний та PR-копірайтинг, ведення блогів, офіційних сторінок бренду у соціальних мережах (SMM-копірайтинг), створення офіційного сайту (інформаційне наповнення та дизайн, UX-копірайтинг, використання елементів LSI-копірайтингу) тощо. Не слід забувати також про взаємозв’язок усіх елементів маркетинг-міксу і, відповідно, функцій копірайтингу, які розглядаються в аспекті цих елементів. Так, ім’я бренду та слоган, які корегуються із маркетинговою продуктовою політикою, є константами рекламних кампаній (маркетингова політика просування). Фірмовий стиль, логотип та фірмовий знак, шрифтові та кольорові рішення відіграють роль також при формуванні ритейл-послуги фірмових магазинів бренду (елемент «Матеріальне середовище») та при створенні брендованих викладок товару бренду у великих ритейлерах. Разом з тим упізнаваний фірмовий блок, офіційний сайт та соціальні сторінки бренду формують фізичний доказ надійності бренду. Таким чином, роль копірайтингу та дизайну відчувається в основному в аспекті таких елементів комплексу маркетингу, як просування, продукт, місце продажу, матеріальне середовище та фізичний доказ. Також важливо розуміти, що усі елементи маркетинг-міксу взаємопов’язані між собою. Відповідно, взаємопов’язані й функції копірайтингу у розрізі окремих елементів комплексу маркетингу, що разом формують маркетингову політику підприємства. The article examines the role and importance of copywriting in the marketing activities of enterprises, examines the points of contact between copywriting/design and marketing in terms of individual elements of the marketing mix. The greatest role of copywriting and design is felt in the formation and implementation of marketing promotion policy: advertising and PR copywriting, blogging, official brand pages in social networks (SMM copywriting), creation of an official website (information content and design, UX copywriting), use elements of LSI copywriting) etc. We should also not forget about the interrelationship of all elements of the marketing mix and, accordingly, the functions of copywriting, which are considered in the aspect of these elements. So, the brand name and slogan, which are adjusted with the marketing product policy, are constants of advertising campaigns (marketing promotion policy). Corporate style, logo and trademark, font and color solutions also play a role in the formation of retail services of the brand's branded stores ("Material environment" element) and in the creation of branded displays of the brand's goods in large retailers. At the same time, a recognizable brand block, the official website and social pages of the brand form physical proof of the reliability of the brand. Thus, the role of copywriting and design is felt mainly in the aspect of such elements of the marketing complex as promotion (advertising and PR copywriting; SMM copywriting, use of LSI copywriting elements; information content of sites, UX copywriting; blogging, etc.), product (naming, creation of a slogan, corporate style, logo and corporate block), place of sale (decoration of corporate stores, font and color solutions, etc.), material environment and physical evidence. It is also important to understand that all elements of the marketing mix are interconnected. Accordingly, the functions of copywriting in terms of separate elements of the marketing complex, which together form the marketing policy of the enterprise, are also interconnected. For example, the slogan and brand name are constants of advertising campaigns, and the official website and social media pages form physical proof of the brand's reliability.
The role and significance of copywriting in marketing
Keywords: копірайтинг; маркетинг; маркетинг-мікс; зв'язок маркетингу й копірайтингу; SMM-копірайтинг; рекламний копірайтинг; LSI-копірайтинг; copywriting; marketing; marketing mix; connection between marketing and copywriting; SMM copywriting; advertising copywriting; LSI copywriting; кафедра маркетингу